New Property Tax Models in Germany — Suitable Paths and Wrong Tracks - Gerhard Graf (Wirtschaftsdienst)
Abstract According to the judgement of the highest constitutional court in Germany in 2018, German states were committed to develop new property tax models in conformity with the constitution. Five states passed new laws last year, which choose the technical size of the plot fort he tax base instead of the value of the property, including buildings. The paper presents the models followed by an evaluation. The final statement refers to an alternative: the substitution of the traditional property tax with a share of the federal income tax and the sales tax for the communities. This alternative offers a simple and quick solution.